Changes in Quality of Diabetes Care and Morbidity over 20 Years in People with Type 1 Diabetes and Long Diabetes Duration: The JEVIN Trial - Heller, T.; Reise, K.; Roth, J.; Lehmann, T.; Schiel, R.; Lorkowski, S.; Müller, U. A.; Müller, N. (Experimental and Clinical Endocrinology & Diabetes, 2017)
Background: The JEVIN trial started as a cross-sectional study in 1989/90 in Jena, a city of the former German Democratic Republic. At that time, the centralized diabetes care system was broken down and restarted 10 years later; structured treatment and teaching programs were implemented, blood glucose self-monitoring, insulin pump-systems and analogue insulin were introduced. We surveyed people with type-1-diabetes of the baseline JEVIN trial in a 20-year follow-up.Methods: 131 patients with type-1-diabetes were analyzed in 1989/90. Of the living population in 2009/10 (n=104), 83 persons were identified and 75 persons with a mean diabetes duration of 35 years were reexamined regarding HbA1c, self-monitoring, diabetes therapy, severe hypoglycemia, diabetic late complications and compared with the results of the same persons in 1989/90.Results: HbA1c decreased from 57.1 mmol/mol in 1989/90 to 52.7 mmol/mol in 2009/10 (7.4 –7.0%; p=0.049). Self-monitoring of blood glucose increased from 2 to 35 tests/week (p<0.001). 100%-use of animal insulin changed to human and analogue insulin therapy. The incidence of severe hypoglycemia increased from 0.1 to 0.16/patient-year. Retinopathy increased from 29 to 69% (p<0.001), nephropathy from 5 to 27% (p<0.001) and neuropathy from 13 to 43% (p<0.001). 17% had no diabetic late complications.Conclusions: The JEVIN trial shows a significant improve in HbA1c in the past 20 years. Severe hypoglycemia occurred rarely and 17% were still free of any diabetic late complication after 35 years of diabetes. This indicates a good quality of diabetes care in a German setting.
Keywords: hypoglycaemia; HbA1c; observational study; Germany; diabetic late complications